„Scena pierwotna” Michèle Le Dœuff: zakaz i pewność siebie w edukacji kobiety [przełożyła Katarzyna Gucio] - Anderson, Pamela Sue (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
The essay begins with Michèle Le Dœuff’s singular account of the “primal scene” in her own education as a woman, illustrating a universally significant point about the way(s) in which education can differ for men and women: gender difference both shapes and is shaped by the imaginary of a culture as manifest in how texts matter for Le Dœuff. Her primal scene is the first moment she remembers when, while aspiring to think for herself, a prohibition is placed in her reading of literature. I propose that “text matters” here not only for gender issues, but for the post-colonial theory which Le Dœuff’s reading of island imagery enhances in western literature and culture. The suggestion is that women in the history of ideas have been more susceptible than men to prohibitions (to reading texts): women’s negative education is against going beyond certain boundaries which have been fixed by a generally colonialist culture on the grounds of gender-hierarchies. I stress the significance of confidence in the production of knowledge. A lack or an inhibition of confidence in one’s own ability to think critically risks the damaging exclusions of, for example, colonialism and sexism. My aim is to unearth the political biases evident in textual imagery, while also pointing to new epistemic locations, with island-and-sea imagery that transgresses patriarchal prohibition, liberating subjects for confident reading and writing of texts today.